Clinical Characterization of a 6-Year-Old Patient with Autism and Two Adjacent Duplications on 10q11.22q11.23. A Case Report - Tritto, Giovanna (Children (Basel), 2021)
Autism is a neurodevelopmental disorder presenting in the first 3 years of life. Deficits occur in the core areas of social communication and interaction and restricted, repetitive patterns of behavior, interests or activities. The causes of autism are unknown, but clinical genetic studies show strong evidence in favor of the involvement of genetic factors in etiology. Molecular genetic studies report some associations with candidate genes, and candidate regions have emerged from several genome-wide linkage studies. Here, we report a clinical case of autism in a 6-year-old boy with double duplication on 10q11.22q11.23 with ASD (Autism Spectrum Disorder), intellectual disability, developmental delay, hypotonia, gross-motor skills deficit, overgrowth and mild dysmorphic features. In the literature, only five cases of ASD with 10q11.21q11.23 duplication are reported. This is the first extensive clinical description of an ASD subject with 10q11.22q11.23 duplication. Our findings suggest that 10q11.21q11.23 microduplication could represent a copy number variant that predisposes to autism.